المفردة القرآنية خصوصيتها الدلالية وخواصُّها البيانية الجمالية - بوخزنة, حمزة (University of Eloued جامعة الوادي, 2014)
الحمد الله رب العالمين و الصلاة و السلام على أشرف المرسلين، وأما بعد: هذا مقال بعنوان : « المفردة القرآنية خُصُوصِيتُها الدلالية وخَواصُّها البيانية الجمالية» تتحدث هذه المقالة عن أحد أبرز العناصر أهمية وأثرا على مستوى النص القرآني، وهي «المفردة القرآنية»؛ فهي المفتاح الدلالي الذي يمكننا من فهم معانية، وكذا الوقوف عند دلائل إعجازه اللغوي. كما تناولت بعض الملامح الدلالية الجمالية التي تتميز بها المفردة في التعبير القرآني. This article entitled: " The Quranic word its privacy semantic and its characteristics rhetorical aesthetic, deals with one of the major elements of paramount importance and effect on the Quranic text level i.e, " The Quranic word" . The latter represents the semantic key that enables us to understand its meanings and know evidences of its linguistic inimitability as well. It also highlighted some of the features aesthetic semantic that the word is characterized in the Quranic expression.
مقال بمجلة البحوث والدراسات
Keywords: النص – القرآن – البيان – الإعجاز – لغة القرآن; text - the Koran - the statement - miracle - the language of the Koran.